2007
DOI: 10.1002/ptr.2105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the growth inhibitory activities of triphala against common bacterial isolates from HIV infected patients

Abstract: The isolation of microbial agents less susceptible to regular antibiotics and the rising trend in the recovery rates of resistant bacteria highlights the need for newer alternative principles. Triphala has been used in traditional medicine practice against certain diseases such as jaundice, fever, cough, eye diseases etc. In the present study phytochemical (phenolic, flavonoid and carotenoid) and antibacterial activities of aqueous and ethanol extracts of Triphala and its individual components (Terminalia cheb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 22 publications
1
35
1
Order By: Relevance
“…In this study, extracts of T. chebula and T. bellerica showed broad spectrum antibacterial activity against all Gram positive and Gram negative organisms and maximum activity was shown against P. acnes and S. epidermidis. The ZOI obtained for extracts of T. chebula and T. bellerica (ZOI: 18-23 mm) in this study were much larger at lower concentration (750 µg) as compared to that obtained by earlier antibacterial studies 44,21,45 . The reason for this variation may be due to difference in geo-climatic and environmental conditions, strain of organism, method of processing, extraction of plant material and assessment of antibacterial activity 46 .…”
Section: Resultscontrasting
confidence: 58%
“…In this study, extracts of T. chebula and T. bellerica showed broad spectrum antibacterial activity against all Gram positive and Gram negative organisms and maximum activity was shown against P. acnes and S. epidermidis. The ZOI obtained for extracts of T. chebula and T. bellerica (ZOI: 18-23 mm) in this study were much larger at lower concentration (750 µg) as compared to that obtained by earlier antibacterial studies 44,21,45 . The reason for this variation may be due to difference in geo-climatic and environmental conditions, strain of organism, method of processing, extraction of plant material and assessment of antibacterial activity 46 .…”
Section: Resultscontrasting
confidence: 58%
“…It is generally accepted that the daily consumption of plantorigin phytochemicals from vegetables, fruits, teas, or herb extracts may regulate the balance of redundant free-radical attacks (1)(2)(3). In the course of screening the active constituents of an immunomodulation from natural resources such as food and/or Oriental herb plants, we found that an aqueous fraction of Perilla frutescens Britton (PfB/af) scored as a good candidate by an in vitro assay (data not shown).…”
Section: Introductionmentioning
confidence: 93%
“…A study was carried out by Srikumar et al [18] on the aqueous and ethanol extracts of Terminalia chebula, Terminalia belerica and Emblica offi cinalis for their antibacterial activity against Pseudomonas aeruginosa, Klebsiella pneumoniae, Shigella sonnei, S. fl exneri, Staphylococcus aureus, Vibrio cholerae, Salmonella paratyphi-B, Escherichia coli, Enterococcus faecalis and Salmonella typhi using the Kirby-Bauer's disk diffusion and MIC methods. T. chebula was found to possess a high phytochemical content, followed by T. belerica and E. offi cinalis in both aqueous and ethanol extracts.…”
Section: Anti-bacterial Effects Including Anti-tuberculous Activity Omentioning
confidence: 99%